Prosecutor's Review of Unlicensed Drug Trafficking Prosecution - Yulinda Apriliyani; Nuvazria Achir (Estudiante Law Journal, 2023)
The purpose of this research is to know and analyze about what is the impact of drug users without a permit at the Bone Bolango State Attorney. The type of research used is empirical research, using data types consisting of primary data and secondary data. Data collection techniques were carried out using interviews, observation, and documentation techniques. The results of the study show that the prosecutor's considerations in imposing criminal charges against the perpetrators in drug distribution cases without a license include objective and subjective considerations. To achieve legal certainty and the purpose of sentencing the accused. The impact of drug distribution without a permit in the Bone Bolango Region is that it is very disturbing to the community and also endangers physical, mental, and social health conditions.